Eşya taşımasında rizikonun sigortalanması - Kepkep, Burak (My University, 2014)
Taşımacılığın farklı yollarla yapılması, uygulamada yük, nakliyat veya emtia taşıma sigortaları olarak da adlandırılan eşya taşıma sigorta sözleşmelerine tek tip ve aynı kuralların uygulanmasını zorlaştırır. Bununla birlikte taşımacılığın türünden bağımsız olarak, sigortacının, sigorta himayesi altına alınan rizikonun gerçekleşmesi sonrasında oluşan zararı tazmin borcu aynı temel kurallara göre belirlenir. Sigortacının oluşan zararı tazmin borcu, geçerli bir sigorta sözleşmesinin varlığına, teminat altına alınan rizikonun sözleşme süresi boyunca mevcudiyetine ve zararın sigorta sözleşmesi ile teminat altına alınan bir rizikonun gerçekleşmesi sonucunda oluşmasına bağlıdır. Zarar sigortalarının tamamında olduğu gibi eşya taşıma sigortalarında da, sözleşme ile sigorta himayesi altına alınan rizikonun zarara sebebiyet verip vermediği, riziko ile oluşan zarar arasındaki nedenselliğin mevcut olmasına bağlıdır. Bu nedenselliğin tespit edilebilmesi, sigorta sözleşmesini oluşturan hükümlerin yorumu ile mümkündür. Bu çalışma ile eşya taşıma sigortalarının tamamına uygulanmakta olan ENSGŞ’nin TBK ve TTK hükümleri karşısındaki geçerliliği ve bunun sigorta himayesine alınan riziko ile oluşan zarar arasındaki nedenselliğe etkileri incelenmiştir. ıma sigorta sözleşmesi; yük sigortası; sigorta genel şartları; rizikonun sigortalanması; emtia nakliyat sigortası genel şartları; Enstitü Yük Klozları; sigorta sözleşmelerinde nedensellik; yorum kuralları; sigorta sözleşmesinin yorumu.

Due to variety of means of transport, it is challenging to set uniform rules for merchandise transport insurance contracts, which are also referred to as cargo, transport or freight insurance policies. Notwithstanding with the foregoing, regardless of the mode of transport chosen, obligation for an insurance company to compensate damages resulting from realization of risks covered by a merchandise transport insurance policy requires existence of the same elements. Accordingly, determination of an insurance company’s obligation to compensate damages depends on existence of a valid (binding) insurance contract, existence of insured risk during the term of this contract; and occurrence of damage from a risk covered by such insurance policy. In merchandise transport insurance policies, to determine whether or not damages actually result from risks that are covered under such insurance policy, causation between the insured risk and damage must be ascertained. This causation is identified and crystallized by enforcing rules of construction (interpretation) against the policy. By this study, we evaluate the validity of general terms and conditions of Turkish merchandise transport insurance policies that are applicable to all means of transport against provisions of the Turkish Code of Obligations No 6098 and Turkish Commercial Code No 6102, and assess the effects to causation between risks covered and damages occurred under an insurance contract. Merchandise transport insurance contract; cargo insurance; insurance of risk; insurance general terms and conditions; general terms and conditions of merchandise transport insurance policies; Institute Cargo Clauses; causation in insurance contracts; rules of construction (interpretation); construction (interpretation) of insurance contracts
Keywords: Hukuk; Hukuk ve Mevzuat; Nakliye Sigortası; Taşıma Hukuku; Taşımacılık; Türkiye